The role of human actors in legitimising informal networked learning of academic digital practice - Johnson, Mike (Proceedings of the International Conference on Networked Learning, 2016)
Ideas from phenomenography inform this study to investigate variation in staff experiences of a decision to introduce digitally shared academic supervision record keeping in a university-based School of Healthcare Sciences in the United Kingdom. At the time, the school's assessment and feedback strategy entitled students to individual formative supervision feedback on all draft essays before submitting them for summative assessment. Prior to the move to a shared digital record, records of supervisory events were stored in individual email inboxes or networked file-store, as well as on paper that was sometimes held in more than one location for the same student. A blogging platform within the university's virtual learning environment was used because, while it allowed students to only view their own records, the whole academic marking team could access any of the students' records. Lave and Wenger's ‘Legitimate Peripheral Participation' provides a theoretical lens for analysis of data collected in interviews with four staff who were selected to represent variations between and within the 'old-timers' and 'new-comers'. The phenomenographic 'outcome space' table is eschewed in favour of a narrative presentation of data that seeks to provide a 'direct encounter' with the phenomena of interest. As such, it represents a case study of informal networked learning, by those on the journey of 'newcomers' from the periphery to full participation and those who guide them. This analysis is challenged by the data, given the varied ways in which staff approached the change to digitally shared supervision record keeping and how the shared records were or were not taken up as a resource to help new staff learn the practice of academic supervision. Staff who had recently moved into academic roles from senior positions in clinical practice experienced dissonance when adjusting to a more permissive information security regime. The study offers insights into the cultural conceptual 'baggage' that can inhibit productive networked learning and the importance of human actors to encourage it and overcome these barriers. The role of students in challenging recalcitrant 'old-timers' into adopting the new digital practice is noted. These actors are held to speak back to theories within networked learning, actor-network theory and Lave and Wenger's communities of practice. The work was undertaken in part fulfilment of a doctorate in e-Research and Technology-Enhanced Learning at Lancaster University.